Antibiotic Resistance in Environmental Microbes: Implementing Authentic Research in the Microbiology Classroom - Tawde, Mangala; Williams, Marianne (Frontiers in Microbiology, 2020)
Incorporating Undergraduate Research Experience in Microbiology Classroom Dr. Mangala Tawde, Associate Professor, Department of Biological Sciences and Geology, Queensborough Community College, CUNY Undergraduate Research (UR) experience is increasingly being recognized as one of the most transforming experiences students can have in their undergraduate years of education. To make it accessible to all students, incorporating authentic research experiences in the classroom is important and it is a major initiative at Queensborough community college; where we have institutionalized UR as a High Impact Practice. We incorporated an authentic research project into the Microbiology course curriculum for allied health majors. The research project was to isolate and identify antibiotic-resistant microbes from diverse environments. As students are aware of antibiotic resistance being a serious concern in today’s medicine, they get interested and are enthusiastically engaged in the research project. Students collect soil samples from various environments and locations of their choice and then they isolate and identify bacteria that may exhibit antibiotic resistance. The microbes isolated from diverse environments are identified based on the 16s rRNA sequence analysis as well as biochemical tests. The research experience is relevant and aligns well with the course curricula, course learning objectives as well as the college’s General Education objectives.